World delirium awareness and quality survey in 2023: a worldwide point prevalence study - Lindroth, Heidi; Liu, Keibun; Szalacha, Laura; Ashkenazy, Shelly; Bellelli, Giuseppe; van den Boogaard, Mark; Caplan, Gideon; Chung, Chi Ryang; Elhadi, Muhammed; Gurjar, Mohan; Heras-La-Calle, Gabriel; Hoffman, Magdalena; et al. (Age & ageing, 2024)
Delirium, an acute brain dysfunction, is proposed to be highly prevalent in clinical care and shown to significantly increase the risk of mortality and dementia.To report on the global prevalence of clinically documented delirium and delirium-related clinical practices in wards caring for paediatric and adult patients in healthcare facilities.A prospective, cross-sectional, 39-question survey completed on World Delirium Awareness Day, 15 March 2023.Clinicians or researchers with access to clinical data.The primary outcome was the prevalence of clinically documented delirium at 8:00 a.m. (4 h) and 8:00 p.m. (±4 h). Secondary outcomes included delirium-related care practices and barriers to use. Descriptive statistics were calculated and multilevel modelling was completed.1664 wards submitted surveys from 44 countries, reporting on delirium assessments at 8:00 a.m. (n = 36 048) and 8:00 p.m. (n = 32 867); 61% reported use of validated delirium assessment tools. At 8:00 a.m., 18% (n = 2788/15 458) and at 8:00 p.m., 17.7% (n = 2454/13 860) were delirium positive. Top prevention measures were pain management (86.7%), mobilisation (81.4%) and adequate fluids (80.4%). Frequently reported pharmacologic interventions were benzodiazepines (52.7%) and haloperidol (46.2%). Top barriers included the shortage of staff (54.3%), lack of time to educate staff (48.6%) and missing knowledge about delirium (38%).In this study, approximately one out of five patients were reported as delirious. The reported high use of benzodiazepines needs further evaluation as it is not aligned with best-practice recommendations. Findings provide a benchmark for future quality improvement projects and research.
Gesehen am 22.04.2025